First records of penicillate millipedes (Diplopoda, Polyxenidae) from Thailand, with descriptions of two new species - Huynh, Cuong; Veenstra, Anneke A; Likhitrakarn, Natdanai (Zootaxa, 2023)
Two new species are described from the family Polyxenidae. Monographis panhai sp. nov. and Unixenus thailandicus sp. nov. represent the first records of their respective genera in Thailand. Monographis panhai sp. nov. shows distinct morphological differences in the arrangement of sensilla in the antennomere VI, as well as in the structures of the labrum and the claw. Collections from different areas of Thailand showed that not only is it widespread but also exhibits geographic variation in morphology. Unixenus thailandicus sp. nov. exhibits sexual dimorphism in the number of conical sensilla on the lateral palp, with 24 in males and 22 in females, differing from the typical count of 13 within the genus.